Carbon Nanotube-Epoxy Nanocomposites: Correlation and Integration of Dynamic Impedance, Dielectric, and Mechanical Analyses. (3rd February 2013) - Moudam, O.; Andrews, T.; Lekakou, C.; Watts, J. F.; Reed, G.
Abstract : This study focuses on the characterization of MWNT-epoxy composites for different MWNT concentrations of 0–7 wt% by correlating different dynamic analysis techniques, including DMA, impedance, and DEA. An optimum composition was established at 0.1 wt% MWNTs corresponding to the best MWNT dispersion which resulted in the formation of an optimum MWNT network. The addition of this low fraction of MWNTs in epoxy resulted in stiffening the molecular structure and suppressing certain molecular transitions, raising the dielectric constant especially in the low-to-medium frequency range, raising the electrical conductivity especially at the high frequencies, and increasing the electromagnetic shielding effectiveness. The 0.1% MWNT-epoxy nanocomposite switched the electromagnetic shielding behaviour from being a very effective absorber at low frequencies to being an effective reflector at high frequencies. Finally, the Nyquist plot derived from the dynamic impedance spectroscopy proved most useful at providing evidence of multiple size distribution of MWNT agglomerates.